Green Tea Leaves As Natural Adsorbent To Remove Pollutants From Shrimp Farm - Wan Nurulatysha, Wan Yusof (2023)
In Malaysia and other nations, pollution of water resources, such as shrimp farms, has been escalating at an alarming rate. Eutrophication was caused by heavy metals and other pollutants that were introduced into shrimp farms, upsetting the aquatic ecosystem and causing health problems. Green tea leaves, which have a high catechin content, a high capacity for adsorption, and are readily available on the market, are one of the promising waste materials that can be utilised to adsorb contaminants from water. Therefore, the goal of this study is to determine how well discarded green tea leaves work to remove contaminants from shrimp farm wastewater. This study involves the preparation of materials, a series of batch experiments, and adsorption isotherm studies. The experiments show that the best contact time is at 10, 20, 30, 40 and 50 min, and the adsorbent dose is 0.2, 0.4, 0.6, 0.8, 1.0 and 1.2g. In overall, this study indicates that waste green tea leaves are a promising alternative adsorbent to adsorb pollutant from shrimp farm wastewater.